1993
DOI: 10.1037/0021-9010.78.6.875
|View full text |Cite
|
Sign up to set email alerts
|

Prediger's dimensional representation of Holland's RIASEC circumplex.

Abstract: The authors conducted a structural meta-analysis to evaluate D. J. Prediger's (1982) 3-factor (1 general factor and 2 bipolar factors of data-ideas and things-people) representation of J. L. Holland's (1985a) RIASEC circumplex (including six personality types: realisticand conventional [C]). Confirmatory factor analysis and multidimensional scaling were applied to 77 U.S. RIASEC correlation matrices published between 1965 and 1989. Prediger's 3-factor model received support when predictions from his factor mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
177
4
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(201 citation statements)
references
References 82 publications
17
177
4
2
Order By: Relevance
“…Using Holland's (1985) familiar (Realistic, Investigative, Artistic, Social, Enterprising, and Conventional; RIASEC) themes, as assessed by the Strong Interest Inventory (Harmon, Hansen, Borgen, & Hammer, 1994), documented a significant degree of temporal stability for these major dimensions of vocational interest over a 15-year time frame from early adolescence to adulthood. Moreover, the structural properties of Holland's hexagon (Rounds & Tracey, 1993) also emerged at age 13. Although Holland's RIASEC system is a widely used framework in counseling psychology, one study using one instrument comes somewhat short of justifying large-scale preference assessments among the gifted in ways commensurate with that currently enjoyed by the SAT.…”
mentioning
confidence: 99%
“…Using Holland's (1985) familiar (Realistic, Investigative, Artistic, Social, Enterprising, and Conventional; RIASEC) themes, as assessed by the Strong Interest Inventory (Harmon, Hansen, Borgen, & Hammer, 1994), documented a significant degree of temporal stability for these major dimensions of vocational interest over a 15-year time frame from early adolescence to adulthood. Moreover, the structural properties of Holland's hexagon (Rounds & Tracey, 1993) also emerged at age 13. Although Holland's RIASEC system is a widely used framework in counseling psychology, one study using one instrument comes somewhat short of justifying large-scale preference assessments among the gifted in ways commensurate with that currently enjoyed by the SAT.…”
mentioning
confidence: 99%
“…On estime actuellement qu'il est plus souhaitable d'élaborer une forme commune accompagnée d'étalonnages différenciés (Dupont, 1987, pp. 522-523 (Prediger & Vansickle, 1992), soit des différences sur les dimensions « sociabilité » et « conformisme » (Rounds & Tracey, 1993).…”
Section: Les Déterminants Des Intérêtsunclassified
“…For similar scales based on the Holland's theory, there are similar little differences in the structure of the RIASEC dimensions. Rounds and Tracey (1993) reported that differences related with the structure of RIASEC based interest inventories may be arisen from the items of the scales and the sample structure may be as strong as the real reason of these differences. Sample structure may affect the range of scores and this situation may change the correlation values and the structure of the RIASEC pattern as well.…”
Section: Personality Types In Turkish Culture 270mentioning
confidence: 99%
“…There are many researches on this subject. Tracey and Rounds (1993) found that Holland's hexagonal model has a low fit rate among non-Americans and ethnic-Americans. Another study by same researchers in 1996 showed that regardless of the analysis type used, Holland's hexagonal model does not support intercultural struct validity.…”
Section: Researcheson Cultural Validity Of Holland's Personality Typementioning
confidence: 99%